Does volume of physical exercise have an effect on depression in patients with fibromyalgia? - Steffens R.D.A.K.* (2017)
© 2016 Elsevier B.V.Background Fibromyalgia Syndrome (FMS) is a musculoskeletal disorder frequently associated with depression. We aimed to investigate the association between physical exercise (PE) and depression in patients with FMS, and to evaluate the effect of the weekly volume of PE on depression. Methods A total of 215 FMS patients with depression were evaluated with the Beck Depression Inventory, and were also classified as inactive, insufficiently active, or active. We performed binary logistic regression, with PE as the dependent variable and the level of depression as an independent variable. We also used the Mann-Whitney U test. An alpha value of 0.05 was determined to have significance (p<0.05). Results Inactive patients with FMS have a higher rate of moderate to severe depression (29.1%) and major depression (25%) when compared with active patients. In comparing the depression index between inactive, insufficiently active, and active FMS patients according to the reported weekly volume of PE, we observed differences between inactive and active patients (p=0.035). The level of depression was positively associated with physical inactivity in FMS, and FMS patients with severe depression had 3.45 1.23–9.64) times the likelihood of being inactive than patients without depression or with minimal depression. Limitations The classification of PE does not distinguish between types of PE, or whether differences in activity can have different results in depression. Conclusion There was an association between PE and lower values of depression in patients with FMS, and the level of depression was positively and significantly associated with physical inactivity.